Use Of Traditional Herbal Medicine, Content Compound Bioactives And Effects His Physiology Is On The Rise Immunity Body : Systematic Literature Review - Muslimah Muslimah; Che Wan Jasimah Bt Wan Mohamed Radzi; Suyadi Suyadi; Ari Yuniastuti; Swasty Swasty; Nina Anggraeni Noviasari; Muhammad Sowwam; Qeyza Naufalia Riz Asmara (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Background: Combination trend​ treatment use herbal and conventional medicines, respectively gradually move going to approach integrative. Use herbal medicine is considered correlated more near with attitudes and beliefs public because can increase immunity body and eliminate worries effect side to drug pharmacy. This is also proven with various type disease that has resolved . Objective: Take inventory use commodity herbal plants and ingredients bioactive as well as study his physiology on the rise immune body. Method: Systematic literature review written based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Search done via ScienceDirect and Sage databases with use related keywords​​ with traditional herbal medicine, content compound bioactive and enhancement immunity body. Collecting data from a database involves keyword combination​ with Boolean operators. A total of 24 articles used as internal data this review study. Result: Various potential herbal medicine for utilized in a way massive including Divya- Swasari -Ras (DSR) with potential overcome asthma; Polygony multiflori For handle intestinal inflammation; Bu Shen Hui Yang Fang (BSHY) for overcome cancer blood leukemia; Skin wood is listed as anti-inflammatory; Ciji- Hua'ai - Baosheng (CHBD) decoction as antitumor; Sinisan For management of chronic hepatitis; Ganoderma lucidum as immunostimulator; Pudilan (PDL) as anti-SARS-COV-2; Carthamus tinctorius L.for handling cardiovascular; Lycium barbarum polysaccharide (LBP) as probiotics; Eucommia ulmoides Oliver as material diabetes medication; Stew Gubenfangxiao (GBFXD) as drug Respiratory; Naodesheng Tablets (NDS) as drug Alzheimer's disease; Astragalus membranaceus (Huangqi (HQ)) for uveitis treatment; Gun-Chil-Jung Capsules (GCJ) as anti cancer; Ligusticum Chuanxiong (Rhizoma chuanxiong) and Borneol ( Borneolum syntheticum) as drug atherosclerosis; Salvia miltiorrhiza Bge.as drug tumor at a time protector endothelium vascular; Tetrastigma hemsleyanum Diels et Gilg for handling injury lungs I; Achyranthis bidentatae For drug disease kidney; Acanthus ilicifolius L., Phyllodium pulchellum (L.) Desv .and Cudrania cochinchinensis Lour.as anti-hepatitis; Epimedium as an antitumor for melanoma, Punica granatum For treatment injury heart; Sanghuangporus sanghuang as anti-inflammatory protector network lungs; and Combretum micranthum as anti-inflammatory . Conclusion: Usage traditional herbal medicine effect on improvement system immune The body is supported by various compound bioactives in these herbal plants .